Accounting, Information Systems, and Underdeveloped Nations. - Seiler, Robert E. (The Accounting Review, 1966)
The article discusses the role of accounting in the development of emerging nations. The author also considers the relationship between the present low level of prestige enjoyed by the accounting professions of these nations and the low rate of their economic growth. The thesis advanced herein is that the strength and extent of the information system of a nation determines in large part the rate at which economic development will progress. In addition, the author observes that accounting and accounting systems thus assume an important role in the development of these nations.